2020
DOI: 10.1021/acs.energyfuels.0c01431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pore Throat Microstructure on Miscible CO2 Soaking Alternating Gas Flooding of Tight Sandstone Reservoirs

Abstract: Miscible CO2-SAG flooding is an improved version of CO2 flooding, which compensates for the insufficient interaction of CO2 and crude oil in the reservoir by adding a CO2 soaking process after the CO2 breakthrough (BT). The transmission of CO2 in the reservoir during the soaking process is controlled by the pore-throat structure of the formation, which in turn affects the displacement efficiency of the subsequent secondary CO2 flooding. In this work, CO2-SAG flooding experiments at reservoir conditions (up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…This paper focuses on the effect of the throat's size and distribution on CO 2 -oil miscible flooding. The mainstream throat contributes 95% to the permeability of core samples, and its radius can be calculated by the following equation (Meng and Liu, 2019;Wang et al, 2020b;Zhong et al, 2021).…”
Section: Methodology Quantitative Characterization Of Microscopic Por...mentioning
confidence: 99%
“…This paper focuses on the effect of the throat's size and distribution on CO 2 -oil miscible flooding. The mainstream throat contributes 95% to the permeability of core samples, and its radius can be calculated by the following equation (Meng and Liu, 2019;Wang et al, 2020b;Zhong et al, 2021).…”
Section: Methodology Quantitative Characterization Of Microscopic Por...mentioning
confidence: 99%
“…Lee and Lee 94 demonstrated that asphaltene precipitation during CO 2 huff and puff in shale reservoirs would reduce porosity and permeability, and shifts wettability toward the oilwet state. Wang et al 103 proposed that after CO 2 soakingalternating-gas (SAG) flooding, asphaltene precipitation leads to permeability reduction, and the damage degree is positively correlated with the heterogeneity of pore microstructure. Compared with CO 2 flooding, it has less damage to the core, especially for the core with poor pore-throat structure.…”
Section: Tight Reservoirsmentioning
confidence: 99%
“…The miscibility process of CO 2 and crude oil is a process in which CO 2 continuously extracts the components of crude oil from light to heavy, and CO 2 continuously dissolves in crude oil . At reservoir temperature, the minimum miscible pressure (MMP) of CO 2 and crude oil is key to determine the miscible flooding effect. In addition, in tight reservoirs, matrix is the main reservoir space of crude oil. However, due to low permeability and small pore diameter of the matrix, an effective displacement system cannot be established in the reservoirs.…”
Section: Introductionmentioning
confidence: 99%